Protocol for Automated Content Analysis of Corpus to Determine Informatics Competencies amongst Health Service Managers - Mark Brommeyer; Mark Mackay; Zhanming Liang; Peter Balan (ACHSM, 2021)
Background: Competencies have emerged as being important to develop health professionals, including managers in healthcare. Professional institutions adopted specific competency frameworks to guide designing professional development opportunities for health service managers, in particularly managers working in the area of health informatics. The fast-growing nature of healthcare settings means that the required competencies continue to evolve. Objective: The aim of this protocol is to outline a reflexive thematic analysis process, including using an automated content analysis approach, and identify what is missing in existing health service management competency empirical studies in relation to health informatics competencies.   Methods: A rapid literature review has been performed using a PRISMA approach for eligibility screening, with 185 publications meeting the inclusion criteria. The Leximancer natural language processing software was used to transform a large corpus of literature from natural language into semantic themes and concepts. A reflexive thematic analysis was then undertaken using the text mining automated content analysis approach to identify predominant concepts and the co-occurrence between them.   Results: A search strategy was developed using three primary electronic databases: 1) Scopus; 2) ProQuest; and 3) the Cumulative Index to Nursing and Allied Health Literature (CINAHL); and five secondary electronic databases: 1) Web of Science 2) PubMed; 3) ACM Digital Library; 4) Open Access Theses and Dissertations Database, and 5) Google Scholar. The initial search undertaken on 10 November 2020 resulted in 1,212 publications. The results of the reflexive thematic analysis will be submitted for publication by November 2021.   Conclusions: New understanding and knowledge in the area of health management competencies, specifically relating to informatics will be developed. Health informatics competencies will be defined for Australian health service managers. Further, this study helps inform the discourse regarding automated content analysis for the healthcare and informatics industry, healthcare organisations and university course requirements.